Ingredients of change : the history and culture of food in modern Bulgaria - Neuburger, Mary, 1966- (Cornell University Press, 2022)
"This book explores the transformation of foodways in modern Bulgaria, through focused chapters on bread, meat, milk, vegetables, and wine. Such ingredients--as the Bulgarian diet itself--changed radically in form and substance in the shadow of changing global and local narratives, practices, and possibilities"--